Introduction to digital economics foundations, business models and case studies - Øverby, Harald; Audestad, Jan Arild (Classroom Companion: Business)
Innovations and developments in technology have laid the foundations for an economy based on digital goods and services the digital economy. This book invites students and practitioners, to take an in-depth look at the impact that technological innovations such as social media, cryptocurrencies, crowdsourcing, and even online gaming is having on today's business landscape. Learn about the various business models available for the digital economy, including the business models used by Bitcoin, Spotify, Wikipedia, World of Warcraft, Facebook, and Airbnb. This book details the evolution of contemporary economics within the digital stratosphere and highlights the complex ecosystem that makes up the field of digital economics. The foundational text with case studies is also peppered with anecdotes on the various technological innovations which have shaped markets throughout history. The authors provide several models and tools that are essential for analysis, as well as activities that will allow the reader to reflect, analyze, and apply the knowledge and tools presented in each chapter. Introduction to Digital Economics is a definitive guide to the complexities and nuances of this burgeoning and fascinating field of study.